Capillary electrophoretic competitive immunoassay with laser-induced fluorescence detection for methionine-enkephalin - Babu, CVS; Chung, BC; Lho, DS; Yoo, YS (ELSEVIER SCIENCE BV, 2006)
Immunoassays are commonly used in bioresearch for the detection and quantification of small proteins and macromolecules in biological fluids and other complex matrices. In this report, a competitive immunoassay using capillary electrophoresis (CE) with laser-induced fluorescence was developed for methionine-enkephalin (ME). The method is based on the competitive reaction between the ME and fluorescein conjugated ME (ME-F) with anti-ME antibody, capillary electrophoresis separation of the ME-antibody bound and free ME-F, followed by the laser-induced fluorescence detection of the fluorescent species. With the optimized separation conditions, it was possible to separate the antibody bound and free fluorescien conjugated ME by a capillary electrophoresis-laser-induced fluorescence (CE-LIF) analysis using an uncoated fused-silica capillaries. The results concluded that the assay specificity, selectivity and accuracy were excellent. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: TANDEM MASS-SPECTROMETRY; ZONE-ELECTROPHORESIS; PROTEIN-G; CHROMATOGRAPHY; NEUROPEPTIDES; ANTIBODY; ASSAY; SEPARATION; PITUITARY; LIGAND